PENGARUH PENAMBAHAN SERBUK BATA MERAH TERHADAP NILAI CBR - Agustian Arif, Muhammad Rayhan; Salimah, A'isyah; Maha Agung, Putera Agung (Prokons: Jurnal Teknik Sipil, 2020)
Abstract Soil is a collection of minerals, organic matter and relatively loose sediments that are located above the bedrock. Based on the particle size, it is divided into four types, namely gravel, sand, silt and clay. The role of soil is very important in a construction because the soil functions as a support for the loads that are above it, so that the soil is expected to have a good bearing capacity. In this study, the soil taken is soft soil in Hambalang, Bogor where the soil conditions in the area are hard in the dry season and soft in the rainy season, so it is necessary to review the CBR (California Bearing Ratio) value. In this study, using waste from red brick as an additive to soft soil. CBR testing is appropriate (SNI 1744: 2012), with the CBR Laboratory test soaked and unsoaked. Along with the addition of% red brick powder, the CBR values of soaked and unsoaked (top and bottom) have increased, so that the addition of% content of red brick powder is 15% respectively got a value of 4.55% and 4.9% (soaked) and 17.94% and 19.70 (unsoaked). So, from this CBR test, it was found that the effect of adding red brick powder increases CBR tilapia soaked and unsoaked soft soil of Hambalang. Keywords: Soft Soil, Red Brick Powder,CBR soaked, CBR unsoaked